Control beliefs can predict the ability to up-regulate sensorimotor rhythm during neurofeedback training - Witte, Matthias; Kober, Silvia E.; Ninaus, Manuel; Neuper, Christa; Wood, Guilherme (Frontiers in Human Neuroscience, 2013)
Technological progress in computer science and neuroimaging has resulted in many approaches that aim to detect brain states and translate them to an external output. Studies from the field of brain-computer interfaces and neurofeedback have validated the coupling between brain signals and computer devices; however a cognitive model of the processes involved remains elusive. Psychological parameters usually play a moderate role in predicting the performance of brain-computer interface (BCI) and neurofeedback (NF) users. The concept of a locus of control, i.e. whether one’s own action is determined by internal or external causes, may help to unravel inter-individual performance capacities. Here, we present data from twenty healthy participants who performed a feedback task based on EEG recordings of the sensorimotor rhythm (SMR). One group of ten participants underwent ten training sessions where the amplitude of the SMR was coupled to a vertical feedback bar. The other group of ten participants participated in the same task but relied on sham feedback. Our analysis revealed that a locus of control score focusing on control beliefs with regard to technology negatively correlated with the power of SMR. These preliminary results suggest that participants whose confidence in control over technical devices is high might consume additional cognitive resources. This higher effort in turn may interfere with brain states of relaxation as reflected in the SMR. As a consequence, one way to improve control over brain signals in neurofeedback paradigms may be to explicitly instruct users not to force mastery but instead to aim at a state of effortless relaxation.